2016
DOI: 10.1007/s10812-016-0271-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Emission from Li2CaSiO4:Dy3+ Phosphors by Doping with Al3+ and B3+

Abstract: Pure Li 2 CaSiO 4 , Li 2 CaSiO 4 :Dy 3+ and Al 3+ , B 3+ co-doped materials were prepared by a solid-state reaction in air at 900 o C for 6 h and characterized by using powder XRD. The luminescence properties of the synthesized phosphors were measured at room temperature with a spectrofl uorometer. Li 2 CaSiO 4 :Dy 3+ emits at 484, 575, and 660 nm upon 352 nm excitation. The emission spectrum intensity of Dy 3+ increased from 0.01 to 0.06 mol.%, and beyond 0.06 mol.%, concentration quenching was observed. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Our recent research on various crystalline oxides revealed a significantly high OCM activity of a quasi‐ternary oxide Li 2 CaSiO 4 (Table ). This oxide was previously investigated as a host material of phosphorous, but its catalytic activity has never been reported. The OCM activity of Li 2 CaSiO 4 is found to be comparable to or even higher than that of the state‐of‐the‐art catalyst Mn−Na 2 WO 4 /SiO 2 .…”
Section: Ch4 Conversion C2 Selectivity and C2 Yield Of Sr2fesbo6 Cmentioning
confidence: 99%
“…Our recent research on various crystalline oxides revealed a significantly high OCM activity of a quasi‐ternary oxide Li 2 CaSiO 4 (Table ). This oxide was previously investigated as a host material of phosphorous, but its catalytic activity has never been reported. The OCM activity of Li 2 CaSiO 4 is found to be comparable to or even higher than that of the state‐of‐the‐art catalyst Mn−Na 2 WO 4 /SiO 2 .…”
Section: Ch4 Conversion C2 Selectivity and C2 Yield Of Sr2fesbo6 Cmentioning
confidence: 99%